Effect of occupational stress on job burnout among coal miners: The mediating role of work-family conflict - Xiaoting YI; Xue LI; Xianting YONG; Jiwen LIU (环境与职业医学, 2022)
BackgroundThe highly prevalent of occupational stress and job burnout of coal miners seriously affect their physical and mental health.ObjectiveTo investigate the levels of occupational stress and job burnout in coal mine workers, and to analyze the mediating effect of work-family conflict between these two conditions.MethodsA total of 1500 coal miners were included by random cluster sampling method from February to October 2019. The levels of occupational stress, work-family conflict, and job burnout of the study participants were evaluated using the Effort-Reward Imbalance Inventory scale (ERI), the Work-Family Conflict Scale, and the Chinese version of the Burnout Scale, and compared among coal miners with different demographic characteristics. Partial correlation analysis was used to find the correlations between indicators; SPSS AOMS 26.0 software was used to analyze the potential mediating effect among occupational stress, work-family conflict, and job burnout in the coal miners in Xinjiang.ResultsThe study included 1247 male coal miners with a valid questionnaire return rate of 83.13%. The M (P25, P75) score of job burnout was 55.00 (47.00, 62.00). Except for gender and monthly income, the differences of job burnout scores among coal miners grouped with selected demographic characteristics were statistically significant (P<0.05). The M (P25, P75) scores of ERI and work-family conflict of coal miners were 1.01 (0.85, 1.21) and 51.00 (44.00, 57.00) respectively, and the differences of ERI and work-family conflict scores among different job types were statistically significant (P<0.05). ERI values were positively correlated with burnout (rs=0.212), emotional exhaustion (rs=0.188), and depersonalization (rs=0.244) scores (all P<0.01); work-family conflict scores were positively correlated with burnout (rs=0.382), emotional exhaustion (rs=0.360), depersonalization (rs=0.370), and reduced sense of accomplishment (rs=0.105) scores (all P<0.01). The regression results showed a significant positive effect of occupational stress on job burnout and work-family conflict (b=7.117, b=8.347, P<0.001), and a mediating effect of work-family conflict on the association between occupational stress and job burnout, with a mediating effect value of 0.249 (50.92% of the total effect of 0.489, P=0.002).ConclusionWork-family conflict may act as a mediating role between occupational stress and job burnout in coal miners, which suggests an indirect effect on occurrence of job burnout.